Seeking shelter in times of crisis? Unemployment, perceived job insecurity and trade union membership - Adrian Chadi; Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2023)
Do trade unions benefit from economic crises by attracting new members among workers concerned about job security? To address this question, we provide a comprehensive empirical investigation based on panel data from Germany, where workers individually decide on their membership. We analyse whether exogenously manipulated perceptions of job insecurity encourage individuals to join a union. Firm-level workforce reductions serve as the first trigger of perceived job insecurity. Regional unemployment rates represent a second source of exogenous variation. Third, we propose a novel identification approach based on plant-closureinduced job losses of other workers in the same region. In each case, we exploit the longitudinal nature of the data to analyse the implications of changes in labour market conditions for changes in union membership using an instrumental-variable approach. We consistently find that perceived job insecurity, as triggered by labour market turmoil, increases the likelihood of individual union membership. Analysing data on media coverage about downsizing in a complementary investigation, we add further evidence to the notion of trade unions as beneficiaries of labour market crises. Finally, we consider workers who lose their jobs and find no evidence of adverse effects on union membership among those directly affected by the labour market situation.
Keywords: D84; J51; J63; 330; Job security; German Socio-Economic Panel; Workforce reduction; Trade union membership; Regional labour markets; Media coverage